Pengaruh Efektivitas Iklan Online Terhadap Minat Beli Pelanggan Bukalapak - Hatta, Holila; Khairunnisa, Siti (Journal of Entrepreneurship, Management and Industry (JEMI), 2020)
This purposed of the study to analyze the effect of the effectiveness of online advertising on buying interest of Bukalapak customers. The data of this study came from distributing questionnaires to 100 respondents who already knew Bukalapak and who knew the Bukalapak Dian Sastro advertisement through social media (youtube). The analysis used in this study is to conduct hypothesis testing using validity, reliability and regression tests. From a series of statistical tests it was concluded that there was a significant effect of the effectiveness of online advertising on customer buying interest for online shopping at Bukalapak. The findings of this study indicate that overall effective advertising has a stronger influence on the desire to shop online.